Respuesta :
3y -2 = 0 is the standard form of the equation.
The standard form of the equation is:
Expression = 0
The expression is always equal to 0. Or in other words, 0 is always on the right, the rest if on the left.
In the above equation: 3y - 7 = -5
Since 0 must be on the left, we transfer -5 to the other side and changed its sign.
3y - 7 + 5 = 0
7 and 5 are whole numbers but have different signs, so the equation is now.
3y - 2 = 0
The standard form of the equation is:
Expression = 0
The expression is always equal to 0. Or in other words, 0 is always on the right, the rest if on the left.
In the above equation: 3y - 7 = -5
Since 0 must be on the left, we transfer -5 to the other side and changed its sign.
3y - 7 + 5 = 0
7 and 5 are whole numbers but have different signs, so the equation is now.
3y - 2 = 0
If you would like to know what is the standard form of the equation 3 * y - 7 = - 5, you can do this using the following two steps:
3 * y - 7 = - 5
3 * y - 7 + 5 = 0
3 * y - 2 = 0
The correct result would be 3 * y - 2 = 0.
3 * y - 7 = - 5
3 * y - 7 + 5 = 0
3 * y - 2 = 0
The correct result would be 3 * y - 2 = 0.